EFEKTIVITAS EKSTRAK DAUN PEPAYA Carica papaya L. TERHADAP JAMUR Alternaria porri PENYEBAB PENYAKIT BERCAK UNGU PADA BAWANG MERAH (Allium ascalonicum L.) SECARA IN VITRO - Zainab, Zainab; Panggeso, Johanis (Fakultas Pertanian, Universitas Tadulako, 2023)
One of the significant diseases afflicting shallots (Allium ascalonicum L) is the purple spot disease (Alternaria porri), leading to substantial harm. The objective of this investigation was to assess the efficacy of papaya leaf extract (Carica papaya L.) against Alternaria porri, the causative agent of purple spot disease in shallots (Allium ascalonicum L.). This research employed a completely randomized design (CRD) with six concentrations of papaya leaf extract (0%, 1%, 2%, 3%, 4%, and 5%) as treatments. The most effective treatment was observed at a 5% extract concentration, which resulted in the slowest expansion of the A. porri colony diameter (1.60 cm) and the most substantial inhibition percentage (77.21%). These outcomes were significantly different from the control treatment, wherein A. porri colony growth reached 6.17 cm and the inhibitory effect was only 16.22%.